TREN SOSIO-SUFISTIK DALAM TAFSIR JAWA: (Pemikiran dan Tren Tafsir Kiai Saleh Darat Semarang Dalam Kitab Faidl al-Rahman)
Tafsir Faidl al-Rahma>n is a work of tafsir written by one of the archipelago scholars of the namely Kiai Saleh Darat, this tafsir is written using the Java language and Arabic pegon script, the goal, in addition as a mean of communication between writers and readers who are Javanese, Java language and the writing of this pegon is also a symbol of resistance against the invaders. The method used in Tafsir Faidl-al-Rahma>n is the analytical method (tah